Flame-retardant aging-resistant polyolefin cable material, preparation method and cable prepared from cable material
By adding modified nano aluminum hydroxide/hexagonal boron nitride nanocomposite powder to the cable material, combining polyethylene and flame retardant, the problem of insufficient flame retardant and scratch resistance of crosslinked polyolefin cable material is solved, and the problem of insufficient flame retardant and scratch resistance of crosslinked polyolefin cable material is achieved. Efficient flame retardant and aging resistance improves, extending cable life.
Patent Information
- Application Number
- CN202411212078.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The flame retardant and scratch-resistant properties of crosslinked polyolefin cable materials are insufficient and cannot meet certain strict safety standards, resulting in a shorter cable service life.
Using a flame-retardant and aging-resistant polyolefin cable material, the ingredients include polyethylene, polyolefin elastomer, organic compatibilizer, modified nano-aluminum hydroxide/hexagonal boron nitride nanocomposite powder and flame retardant, through mixing and modification The addition of nano-aluminum hydroxide/hexagonal boron nitride nanocomposite powder improves the flame retardant and scratch-resistant performance of the cable.
It significantly improves the flame retardant and aging resistance of the cable, extends the service life of the cable, and maintains excellent electrical performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of electric wires and cables, and in particular to a flame-retardant and aging-resistant polyolefin cable material, a preparation method and a cable made from the cable material. Background Art
[0002] In the cable industry, cross-linked polyolefin materials are widely used due to their excellent electrical properties and good mechanical strength. Although cross-linked polyolefin occupies an important position in cable applications, it still has some performance limitations. First, the flame retardancy of cross-linked polyolefin materials is not enough to meet certain strict safety standards. Second, the lack of scratch resistance of cross-linked polyolefin materials may cause sheath damage and shorten the service life of the cable. Therefore, there is an urgent need for a cable with strong scratch resistance and high flame retardancy to keep its electrical properties unaffected. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a flame retardant and aging-resistant polyolefin cable material, a preparation method and a cable made from the cable material, aiming to solve the problem of insufficient scratch resistance and flame retardancy of current cross-linked polyolefin cables.
[0004] To achieve the above-mentioned purpose, the present invention proposes a flame-retardant and aging-resistant polyolefin cable material. The ingredients of the flame-retardant and aging-resistant polyolefin cable material, measured by weight, include: 20-40 parts of polyethylene; 20-30 parts of polyolefin elastomer; 5-10 parts of organic compatibilizer; 5-15 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; and 10-30 parts of flame retardant.
[0005] Optionally, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is 8-12 parts.
[0006] Optionally, the polyethylene includes 15-30 parts of high-density polyethylene and 5-10 parts of linear low-density polyethylene.
[0007] Optionally, the polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer and ethylene-octene copolymer.
[0008] Optionally, the organic compatibilizer is at least one of polyethylene grafted with maleic anhydride, polypropylene grafted with maleic anhydride, a copolymer of styrene and maleic anhydride, and polyolefin elastomer grafted with maleic anhydride.
[0009] Optionally, the flame retardant is a compound of an organic flame retardant and an inorganic flame retardant, and the weight ratio of the organic flame retardant to the inorganic flame retardant is (0-10): (10-20).
[0010] Optionally, the flame retardant and aging resistant polyolefin cable material further comprises a lubricant, and the lubricant is at least one of fatty acids, aliphatic amides, metal soaps and fatty alcohols.
[0011] Optionally, the flame-retardant and aging-resistant polyolefin cable material also includes an antioxidant, which is at least one of bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetrakis(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5-methylphenyl]2,4,8,10-tetraoxaspiro[5,5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)ester), 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicyl phthalimide.
[0012] Optionally, the flame retardant and aging-resistant polyolefin cable material also includes a crosslinking aid, which is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, N,N-phenylbismaleimide, zinc diacrylate and zinc dimethacrylate.
[0013] In order to achieve the above-mentioned purpose, the present invention also proposes a method for preparing a flame-retardant and aging-resistant polyolefin cable material, comprising the following steps: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method from hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; preparing flame-retardant and aging-resistant polyolefin cable material: pre-mixing polyethylene, polyolefin elastomer, organic compatibilizer, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, flame retardant, lubricant, antioxidant and cross-linking aid, and then mixing them in an internal mixer to prepare a molten blend; granulating the molten blend in a twin-screw-single-screw hot-cut air-cooled granulation unit, followed by secondary air cooling and vibration screening, and finally obtaining a flame-retardant and aging-resistant polyolefin cable material.
[0014] Optionally, the preparation method of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: exfoliating hexagonal boron nitride to form hexagonal boron nitride nano sheets and hydroxylating the sheets to obtain micro-nano hexagonal boron nitride powder, then in situ growing nano aluminum hydroxide on the surface of the micro-nano hexagonal boron nitride powder to obtain nano aluminum hydroxide / hexagonal boron nitride nano composite powder, then adding the nano aluminum hydroxide / hexagonal boron nitride nano composite powder and a silane coupling agent to an ethanol solution, and drying after ultrasonic dispersion and vacuum filtration to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder.
[0015] Optionally, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0016] In order to achieve the above object, the present invention also provides a cable, which is made of any one of the above-mentioned flame-retardant and aging-resistant polyolefin cable materials.
[0017] Beneficial effects of the present invention: In the present invention, polyethylene, polyolefin elastomer, organic compatibilizer and flame retardant are mixed together as a mixed elastomer component of flame retardant and aging-resistant polyolefin cable material. By adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, not only the scratch resistance of the substrate can be improved, but also the deformation resistance of the sheath material can be improved. After adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, the flame retardant effect of the flame retardant and aging-resistant polyolefin cable material can be improved to a certain extent, thereby realizing the composite modification of the flame retardant and aging-resistant polyolefin cable material, so that it obtains excellent aging resistance. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0019] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0020] In the cable industry, cross-linked polyolefin materials are widely used due to their excellent electrical properties and good mechanical strength. Although cross-linked polyolefin occupies an important position in cable applications, it still has some performance limitations. First, the flame retardancy of cross-linked polyolefin materials is not enough to meet certain strict safety standards. Second, the lack of scratch resistance of cross-linked polyolefin materials may cause sheath damage and shorten the service life of the cable. Therefore, there is an urgent need for a cable with strong scratch resistance and high flame retardancy to keep its electrical properties unaffected.
[0021] To solve the above problems, the present invention proposes a flame retardant and aging-resistant polyolefin cable material. The ingredients of the flame retardant and aging-resistant polyolefin cable material, measured by weight, include: 20-40 parts of polyethylene; 20-30 parts of polyolefin elastomer; 5-10 parts of organic compatibilizer; 5-15 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; and 10-30 parts of flame retardant.
[0022] In the present invention, polyethylene, polyolefin elastomer, organic compatibilizer and flame retardant are mixed together as a mixed elastomer component of flame retardant and aging-resistant polyolefin cable material. By adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, not only the scratch resistance of the substrate can be improved, but also the deformation resistance of the sheath material can be improved. After adding modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, the flame retardant effect of the flame retardant and aging-resistant polyolefin cable material can be improved to a certain extent, thereby realizing the composite modification of the flame retardant and aging-resistant polyolefin cable material, so that it obtains excellent aging resistance.
[0023] In some embodiments, the ingredients of the flame retardant and aging resistant polyolefin cable material, measured in parts by weight, preferably include: 20-40 parts of polyethylene; 20-30 parts of polyolefin elastomer; 5-10 parts of organic compatibilizer; 5-15 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; and 10-30 parts of flame retardant.
[0024] Furthermore, 8-12 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder.
[0025] In some embodiments, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is preferably 8 parts.
[0026] In some embodiments, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is preferably 12 parts.
[0027] Furthermore, the polyethylene includes 15-30 parts of high-density polyethylene and 5-10 parts of linear low-density polyethylene.
[0028] In some embodiments, the melt flow rate of the high density polyethylene is 5-15 g / 10 min at 190° C. / 2.16 kg under test conditions, and the melt flow rate of the linear low density polyethylene is 5-10 g / 10 min at 190° C. / 2.16 kg under test conditions.
[0029] Furthermore, the polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer or ethylene-octene copolymer.
[0030] In some embodiments, the polyolefin elastomer is preferably ethylene-methyl acrylate copolymer.
[0031] In some embodiments, the polyolefin elastomer is preferably a mixture of ethylene-butene copolymer and ethylene-octene copolymer.
[0032] Furthermore, the organic compatibilizer is at least one of polyethylene grafted with maleic anhydride, polypropylene grafted with maleic anhydride, a copolymer of styrene and maleic anhydride, and polyolefin elastomer grafted with maleic anhydride.
[0033] Maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, copolymers of styrene and maleic anhydride, or maleic anhydride grafted polyolefin elastomers as organic compatibilizers can effectively reduce the size of the dispersed phase, keep the phase structure unchanged, reduce the surface tension between the polymers, improve the mechanical properties of the mixed materials, ensure the mechanical properties of flame-retardant and aging-resistant polyolefin cable materials, and reduce the interaction between the components, ensuring the uniformity and stability of the mixed materials such as polyethylene, polyolefin elastomers and flame retardants.
[0034] In some embodiments, the organic compatibilizer is preferably polyethylene grafted with maleic anhydride.
[0035] Furthermore, the flame retardant is a compound of an organic flame retardant and an inorganic flame retardant, and the weight ratio of the organic flame retardant to the inorganic flame retardant is (0-10): (10-20).
[0036] The flame retardant is a compound of organic flame retardant and inorganic flame retardant. Compared with single-component flame retardant, this flame retardant utilizes multiple flame retardant elements to make up for the deficiency of a single flame retardant element, thereby better balancing the relationship between flame retardant dosage, performance and cost, and is more environmentally friendly and safe.
[0037] In some embodiments, the organic flame retardant is at least one of a phosphorus-based flame retardant and a nitrogen-based flame retardant.
[0038] In some embodiments, the inorganic flame retardant is at least one of magnesium hydroxide and aluminum hydroxide.
[0039] In some embodiments, the flame retardant is a compound of an organic flame retardant and an inorganic flame retardant, and the weight ratio of the organic flame retardant to the inorganic flame retardant is 5:20.
[0040] Furthermore, the flame retardant and aging resistant polyolefin cable material also includes a lubricant, and the lubricant is at least one of fatty acids, fatty amides, metal soaps and fatty alcohols. In some embodiments, the lubricant is preferably 0.5 parts of a fatty acid-based lubricant.
[0041] Furthermore, the flame retardant and aging resistant polyolefin cable material also includes an antioxidant, which is at least one of bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetrakis(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5-methylphenyl]2,4,8,10-tetraoxaspiro[5,5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)ester), 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicyl phthalimide.
[0042] In some embodiments, the antioxidant is preferably 0.5 parts of bis(octadecyl)hydroxylamine.
[0043] Furthermore, the flame-retardant and aging-resistant polyolefin cable material also includes a crosslinking aid, which is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, N,N-phenylbismaleimide, zinc diacrylate and zinc dimethacrylate.
[0044] In some embodiments, the crosslinking aid is preferably 2 parts of trimethylolpropane triacrylate.
[0045] Lubricants can improve fluidity during processing, increase the impact strength of materials, reduce water absorption on the cable surface, improve cable scratches and surface defects, and reduce heat release rate and smoke generation, all of which help to improve cable performance and safety. Adding antioxidants can prevent thermal oxidative degradation of elastomers. Cross-linking aids can significantly improve the material's heat resistance, aging resistance, electrical properties, and mechanical properties by promoting cross-linking between polyethylene molecular chains.
[0046] In order to solve the above problems, the present invention also provides a method for preparing a flame retardant and aging resistant polyolefin cable material, comprising the following steps: S1: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; In this scheme, the hexagonal boron nitride in the modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder is treated to obtain a micro-nano hexagonal boron nitride, which has the characteristics of both nanomaterials and micron fillers. First, the micron sheet filler can improve the scratch resistance of the matrix due to the low friction coefficient of hexagonal boron nitride itself; secondly, the structure of the nanosheet makes the subsequent growth of nano-aluminum hydroxide, and the specific surface area of the nano-aluminum hydroxide generated in situ on the surface of the hexagonal boron nitride nanosheet is large, which reduces the partial pressure of water vapor on the particle surface, and can improve the flame retardant effect to a certain extent. In addition, due to the excellent thermal conductivity and thermal stability of hexagonal boron nitride, it can improve the heat resistance of nano-aluminum hydroxide, so the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression, and the use of flame retardants in combination can reduce its dosage and achieve excellent flame retardant effects. Finally, the sheet structure of micro-nano hexagonal boron nitride can also change the path of oxygen, moisture, etc. entering the resin matrix, thereby improving the aging resistance.
[0047] S2: preparing flame-retardant and aging-resistant polyolefin cable material: pre-mixing polyethylene, polyolefin elastomer, organic compatibilizer, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, flame retardant, lubricant, antioxidant and cross-linking aid, and then mixing in an internal mixer to prepare a molten blend; In some embodiments, internal mixing is performed in an internal mixer.
[0048] S3: The molten blend is granulated by extrusion, followed by air cooling and screening to finally obtain a flame retardant and aging resistant polyolefin cable material.
[0049] In some embodiments, extrusion granulation is achieved by a twin-screw-single-screw hot-cut air-cooled granulation unit.
[0050] In some embodiments, the radiation cross-linked polyolefin material is irradiated using an 18 Mrad electron beam.
[0051] Furthermore, the preparation method of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.
[0052] In some embodiments, hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonicated for 24 hours using an ultrasonic disperser at a power of 500 W. After vacuum filtration, the solution is dried in a vacuum oven at 80-100° C. for 6-8 hours to obtain micro-nano hexagonal boron nitride powder.
[0053] In some embodiments, aluminum chlorohydrate is dissolved in n-butanol solution, and then hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filtration is performed and deionized water is used to wash 5-8 times until the Cl - .
[0054] In some embodiments, nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and a silane coupling agent are added to an ethanol solution, ultrasonically dispersed at 40-80°C with a power of 120W for 4 hours, followed by vacuum filtration and drying in a vacuum oven at 70-90°C for 24-30 hours to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder.
[0055] Furthermore, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0056] In some embodiments, the silane coupling agent is preferably 3-aminopropyltriethoxysilane.
[0057] In order to solve the above problems, the present invention further provides a cable, which is prepared by the above method for preparing the flame-retardant and aging-resistant polyolefin cable material.
[0058] The content of the present invention is explained below through specific examples and data.
[0059] Embodiment 1: The hexagonal boron nitride is peeled off to form hexagonal boron nitride nanosheets and hydroxylated. The hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonically dispersed at 500w for 24 hours, vacuum filtered and dried in a vacuum oven at 80-100℃ for 6-8 hours to obtain micro-nano hexagonal boron nitride powder. Secondly, nano aluminum hydroxide is grown in situ on the surface of hexagonal boron nitride nanosheets. Aluminum chlorohydrate is dissolved in n-butanol solution, and the hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filter again and wash with deionized water 5-8 times to clean Cl - Then, the nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and the silane coupling agent were added to the ethanol solution, and ultrasonicated at 40-80° C. with a power of 120 W for 4 h using an ultrasonic disperser, followed by vacuum filtration and drying in a vacuum oven at 70-90° C. for 24-30 h, and finally the modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder was obtained.
[0060] 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and then extruded and granulated to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0061] Embodiment 2: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 8 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0062] Embodiment 3: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 10 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0063] Embodiment 4: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 12 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0064] Embodiment 5: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 15 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0065] Embodiment 6: The preparation method is the same as that of Example 1, except that: 30 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0066] Embodiment 7: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 15 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material.
[0067] Embodiment 8: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 5 parts of organic flame retardant, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded into granules to obtain granular materials.
[0068] Embodiment 9: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of organic flame retardant, 10 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded into granules to obtain granular materials.
[0069] Comparative Example 1: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and then extruded and granulated to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0070] Comparative Example 2: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 10 parts of organic flame retardant, 10 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and then extruded and granulated to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0071] Comparative Example 3: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of untreated hexagonal boron nitride, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and then extruded and granulated to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0072] Comparative Example 4: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 5 parts of modified hexagonal boron nitride, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and kneaded, and then extruded and granulated to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0073] Comparative Example 5: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 1 part of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0074] Comparative Example 6: The preparation method is the same as that of Example 1, except that: 20 parts of high-density polyethylene, 5 parts of linear low-density polyethylene, 20 parts of polyolefin elastomer, 6 parts of organic compatibilizer, 20 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 20 parts of inorganic flame retardant, 1 part of lubricant, 1 part of antioxidant and 2 parts of cross-linking aid are mixed and extruded to obtain granular material; The granular material is irradiated by an 18Mrad electron beam to obtain a flame-retardant and aging-resistant polyolefin cable material.
[0075] The components and important preparation variables of Examples 1-9 and Comparative Examples 1-6 are summarized in Table 1.
[0076] Table 1. Components of Examples 1-9 and Comparative Examples 1-6 of the present invention
[0077] According to relevant test standards, the flame retardant and aging-resistant polyolefin cable materials in the above Examples 1-9 and Comparative Examples 1-6 were tested for tensile strength, elongation at break, flame retardant grade and scratch resistance times, and the test results were recorded in the following Table 2: Table 2. Performance of Examples 1-9 and Comparative Examples 1-6
[0078] According to the above test results, it can be seen that in Examples 1-5, the added amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder gradually increases within the range of 5-15 parts by weight of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in the present invention. The added amounts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in Examples 1-5 are 5 parts, 8 parts, 10 parts, 12 parts and 15 parts, respectively. Compared with Examples 1-5, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in Comparative Example 5 is 1 part, and the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in Comparative Example 6 is 20 parts, both of which are not in the present invention. The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is within the range of 3-10 parts by weight. The test results of comparative examples 1-5 and comparative examples 5-6 show that in the present invention, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is within the range of 5-15 parts by weight. The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder can improve the flame retardant efficiency of the organic flame retardant and reduce the amount of the flame retardant, and within this range, as the amount of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder increases, the mechanical properties and flame retardancy of the prepared flame retardant and aging-resistant polyolefin cable material are also improved; the tensile strength of Example 1 is 1 7.6MPa, elongation at break is 482%, tensile strength after aging is 90MPa, elongation at break is 92%, flame retardant grade is V-0, scratch resistance is 382 times, comparative example 3 changes 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder to 5 parts of untreated hexagonal boron nitride, comparative example 4 changes 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder to 5 parts of modified hexagonal boron nitride, the tensile strength of comparative example 3 is 11.3MPa, elongation at break is 300%, the tensile strength after aging is 81MPa, elongation at break is 82%, flame retardant grade is V-1, scratch resistance is 1 36 times, the tensile strength of comparative example 4 is 16.8MPa, the elongation at break is 426%, the tensile strength after aging is 87MPa, the elongation at break is 86%, the flame retardant grade is V-1, and the scratch resistance number is 353 times. It can be concluded from the experimental data that compared with Example 1 with the addition of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder, the tensile strength, elongation at break, retention rate after aging, flame retardant grade and scratch resistance number of Examples 3-4 are all poor. Therefore, the cross-linked polyolefin material with the addition of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder can achieve the improvement of flame retardancy, scratch resistance and aging resistance.When the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is used in combination with other flame retardants, the efficiency of the flame retardant can be improved, the amount of the flame retardant can be reduced, and an excellent flame retardant effect can be achieved. In addition, the flaky structure of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder can also change the path for oxygen, moisture, etc. to enter the resin matrix, thereby improving the aging resistance. Therefore, the cross-linked polyolefin material proposed in the present invention has the characteristics of low smoke and halogen-free flame retardancy and excellent scratch resistance and aging resistance, and is suitable for the manufacture of various automotive cables.
[0079] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A flame retardant and aging resistant polyolefin cable material, characterized in that: The ingredients of the flame retardant and aging resistant polyolefin cable material include, by weight: 20-40 parts of polyethylene; Polyolefin elastomer 20-30 parts; 5-10 parts of organic compatibilizer; 5-15 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; Flame retardant 10-30 parts.
2. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is 8-12 parts.
3. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The polyethylene comprises 15-30 parts of high-density polyethylene and 5-10 parts of linear low-density polyethylene.
4. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer and ethylene-octene copolymer.
5. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The organic compatibilizer is at least one of polyethylene grafted with maleic anhydride, polypropylene grafted with maleic anhydride, copolymerization of styrene and maleic anhydride, and polyolefin elastomer grafted with maleic anhydride.
6. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The flame retardant is a compound of an organic flame retardant and an inorganic flame retardant, and the weight ratio of the organic flame retardant to the inorganic flame retardant is (0-10): (10-20).
7. The flame retardant and aging resistant polyolefin cable material according to claim 1, characterized in that: The flame retardant and aging resistant polyolefin cable material also includes a lubricant, and the lubricant is at least one of fatty acids, aliphatic amides, metal soaps and fatty alcohols.
8. The flame-retardant and aging-resistant polyolefin cable material according to claim 1, characterized in that: The flame-retardant and aging-resistant polyolefin cable material also includes an antioxidant, which is at least one of bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetrakis(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5-methylphenyl]2,4,8,10-tetraoxaspiro[5,5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)ester), 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicyl phthalimide.
9. The flame-retardant and aging-resistant polyolefin cable material according to claim 1, characterized in that: The flame-retardant and aging-resistant polyolefin cable material also includes a crosslinking aid, which is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, N,N-phenyl bismaleimide, zinc diacrylate and zinc dimethacrylate.
10. A method for preparing a flame-retardant and aging-resistant polyolefin cable material, characterized in that: The following steps are involved: Preparation of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using hexagonal boron nitride, isopropyl alcohol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; Preparation of flame-retardant and aging-resistant polyolefin cable material: polyethylene, polyolefin elastomer, organic compatibilizer, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, flame retardant, lubricant, antioxidant and cross-linking aid are pre-mixed uniformly, and then mixed in an internal mixer to prepare a molten blend; the molten blend is granulated in a twin-screw-single-screw hot-cut air-cooled granulation unit, followed by secondary air cooling and vibration screening to finally obtain a flame-retardant and aging-resistant polyolefin cable material.
11. The method for preparing the flame-retardant and aging-resistant polyolefin cable material according to claim 10, characterized in that: The method for preparing the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.
12. The method for preparing the flame-retardant and aging-resistant polyolefin cable material according to claim 11, characterized in that: The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
13. A cable, characterized in that: The cable is made from the cable material according to claim 1.
Citation Information
Patent Citations
125 DEG C irradiation crosslinking type halogen-free flame-retardant polyolefin cable material for photovoltaic cable and preparation method thereof
CN111234358A
Halogen-free flame-retardant polyolefin cable material for automobile and preparation method thereof
CN113912928A
Low-dielectric heat-conducting phase change gasket and preparation method thereof
CN118978895A
Novel cross-linked separator and preparation method thereof, battery, and electronic device
WO2023087735A1
Cited By
Cable for energy storage system and energy storage system
CN117275822A
Flexible flame-retardant polyolefin insulating material for high-flexibility drag chain cable as well as preparation method and application of flexible flame-retardant polyolefin insulating material
CN119350741A
Flame-retardant polyolefin cable material and preparation method thereof
CN119708711A
Anti-interference oil-resistant wear-resistant control cable
CN120089444A
High-temperature-oil-resistant polyolefin material for motor wire and preparation method of high-temperature-oil-resistant polyolefin material
CN120535860A
